Thermo-mechanical modelling of the Friction Stir Spot Welding process: Effect of the friction models on the heat generation mechanisms. (August 2022) - Hannachi, Nasra; Khalfallah, Ali; Leitão, Carlos; Rodrigues, Dulce
Friction Stir Spot Welding involves complex physical phenomena, which are very difficult to probe experimentally. In this regard, the numerical simulation may play a key role to gain insight into this complex thermo-mechanical process. It is often used to mimic specific experimental conditions to forecast outputs that may be substantial to analyse and elucidate the mechanisms behind the Friction Stir Spot Welding process. This welding technique uses frictional heat generated by a rotating tool to join materials. The heat generation mechanisms are governed by a combination of sliding and sticking contact conditions. In the numerical simulation, these contact conditions are thoroughly dependent on the used friction model. Hence, a successful prediction of the process relies on the appropriate selection of the contact model and parameters. This work aims to identify the pros and cons of different friction models in modelling combined sliding-sticking conditions. A three-dimensional coupled thermo-mechanical FE model, based on a Coupled Eulerian-Lagrangian formulation, was developed. Different friction models are adopted to simulate the Friction Stir Spot Welding of the AA6082-T6 aluminium alloy. For these friction models, the temperature evolution, the heat generation, and the plastic deformation were analysed and compared with experimental results. It was realized that numerical analysis of Friction Stir Spot Welding can be effective and reliable as long as the interfacial friction characteristics are properly modelled. This approach may be used to guide the contact modelling strategy for the simulation of the Friction Stir Spot Welding process and its derivatives.